Switching-on luminescence in anilate-based molecular materials1. Issue 36 (28th September 2015) - Atzori, Matteo; Artizzu, Flavia; Marchiò, Luciano; Loche, Danilo; Caneschi, Andrea; Serpe, Angela; Deplano, Paola; Avarvari, Narcis; Mercuri, Maria Laura
<x xml:space="preserve">Abstract</x> A simple substituent exchange on the chloranilate ligand induces unprecedented luminescence properties in the class of anilate ligands and their metal complexes.